Do farmers and conservationists perceive landscape changes differently? - Noémi Ujházy (Resilience Alliance, 2020)
Broader understanding of stakeholders' perceptions of landscape changes is needed to cope with global environmental challenges locally. In this study, farmers' and conservationists'-researchers' perceptions of landscape changes were compared by analyzing interviews conducted in the Danube-Tisza Interfluve region of Hungary through a combined quantitative and qualitative approach. Perceptions concerning the trends of changes (increasing or decreasing), as well as evaluations (positive and negative) of 40 different landscape elements were analyzed. The quantitative analysis consisted of landscape elements of different native and alien plant and animal species, natural habitats, and types of land use. For a qualitative analysis, one landscape element, the tussock sedge beds, a type of wetland habitat, was chosen. According to the quantitative analysis, the two groups held similar views on trends. However, their evaluations differed substantially. The most significant differences appeared between the two groups in cases where land use and biodiversity goals were in competition, e.g., abandonment and non-native plantations. Changes causing both decline of biodiversity and the fading of the cultural landscapes were seen similarly negatively by the two groups, e.g., disappearance of lakes, spread of invasive plants, expansion of wild boar. However, quantitative analysis also showed that conservationists-researchers had higher consensus, while farmers were much more diverse in their evaluations. Qualitative analysis explored the reasons for these differences. Although conservationists-researchers shared eco-centric values, farmers evaluated landscape changes heterogeneously based on individual constellations of economic interest, cultural values, and their sense of responsibility for nature. Our study, with the combined application of quantitative and qualitative analyses, provides new understandings of both between-group and within-group differences and similarities of farmers' and conservationists'-researchers' landscape change perceptions.